Association between serum polyunsaturated fatty acids and bone mineral density in US adults: NHANES 2011-2014 - Liang, Hao; Xiong, Chuang; Luo, Yuangang; Zhang, Jun; Huang, Yanran; Zhao, Runhan; Zhou, Nian; Zhao, Zenghui; Luo, Xiaoji (Frontiers in Endocrinology, 2023)
Objective: The purpose of this study was to investigate the association between serum polyunsaturated fatty acids (PUFAs) and bone mineral density (BMD).Methods: We performed a cross-sectional study based on data from the National Health and Nutrition Examination Survey (NHANES) 2011-2014. The weighted multiple linear regression model was utilized to determine the association between serum PUFAs and BMD. Further smoothed curve fitting and threshold effect analysis were conducted. Finally, we performed a subgroup analysis.Results: In total, 1979 participants aged 20-59 years were enrolled. After adjusting for all covariates, we found that serum docosapentaenoic acid (DPA) was positively associated with head BMD (β = 0.0015, 95% Cl: 0.0004, 0.0026, P = 0.008296) and lumbar spine BMD (β = 0.0005, 95% Cl: 0.0000, 0.0010, P = 0.036093), and serum eicosadienoic acid (EDA) was negatively associated with thoracic spine BMD (β = -0.0008, 95% Cl: -0.0016, -0.0000, P = 0.045355). Smoothed curve fitting revealed a nonlinear positive association between serum DPA and lumbar spine BMD. Threshold effect analysis indicated that the threshold of serum DPA was 81.4 µmol/L. Subgroup analysis revealed a positive correlation between serum DPA and head BMD in the subgroup aged 50-59 years (β = 0.0025, 95% Cl: 0.0002, 0.0049, P = 0.035249) and females (β = 0.0026, 95% Cl: 0.0008, 0.0044, P = 0.005005). There was a positive relationship between serum DPA and lumbar spine BMD in females (β = 0.0008, 95% Cl: 0.0001, 0.0015, P = 0.017900) and a negative association between serum EDA and thoracic spine BMD in the subgroup aged 30-39 years (β = -0.0016, 95% Cl: -0.0031, -0.0001, P = 0.041331), 2 This is a provisional file, not the final typeset article males (β = -0.0012, 95% Cl: -0.0023, -0.0001, P = 0.039364) and other races (β = -0.0021, 95% Cl: -0.0037, -0.0006, P = 0.008059).Conclusions: This study demonstrated a linear positive relationship between serum DPA and head BMD, a nonlinear positive association between serum DPA and lumbar spine BMD, and a linear negative correlation between serum EDA and thoracic spine BMD in US adults.